Science Learning Trends in Elementary Schools 2015–2025: A Review - Siti Patonah; Aprilya Ihwal Atinah (Postgraduate, University of Mataram, 2026)
This study aims to identify trends in instructional models, research variables, learning materials, subject characteristics, and research outcomes in elementary science (IPA) education through a meta-analysis of 30 peer-reviewed articles published between 2015 and 2025. Articles were selected based on specific inclusion criteria and analyzed using descriptive qualitative content analysis. The findings reveal that Problem Based Learning (PBL) is the most frequently used instructional model (18 articles), consistently demonstrating effectiveness in improving student learning outcomes, critical thinking, motivation, creativity, and problem-solving skills. Other models used include Project Based Learning (6 articles), Discovery Learning (3 articles), and several others such as Inquiry-Based Learning and Teams Games Tournament. Most studies focus on cognitive variables, particularly learning outcomes and critical thinking, while affective aspects like motivation and scientific attitudes remain underexplored. Furthermore, several studies either vaguely reported or did not specify the learning materials used, indicating a gap in methodological reporting. In terms of subject characteristics, 73.30% of the studies did not mention gender composition, suggesting limited attention to student demographics. Despite these gaps, the overall analysis shows that the implementation of innovative learning models has a positive impact on elementary science education, especially in enhancing students’ academic performance. These findings highlight the importance of adopting student-centered learning approaches and improving research transparency in reporting instructional contexts and subject characteristics